2018
DOI: 10.1038/s41467-018-03638-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of CSF1R-dependent macrophages in control of the intestinal stem-cell niche

Abstract: Colony-stimulating factor 1 (CSF1) controls the growth and differentiation of macrophages.CSF1R signaling has been implicated in the maintenance of the intestinal stem cell niche and differentiation of Paneth cells, but evidence of expression of CSF1R within the crypt is equivocal. Here we show that CSF1R-dependent macrophages influence intestinal epithelial differentiation and homeostasis. In the intestinal lamina propria CSF1R mRNA expression is restricted to macrophages which are intimately associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 65 publications
(135 reference statements)
5
148
0
Order By: Relevance
“…Another population of macrophages detected in our analyses is CD206-positive macrophages, which are located at the base of crypts (Fig 6), express MafB (Fig 6) and IL10 (Supplementary Fig S5). These macrophages are likely to represent fully differentiated tolerogenic macrophages involved in sensing luminal antigen via sampling between intestinal epithelial cells, and contributing to epithelial renewal via the regulation of Lgr5 + stem cells 13,61 . The Cd206 macrophages appeared largely unaffected by IRF5 deficiency (Fig 7) and unlikely to be major contributors to the Hh-induced pathology 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Another population of macrophages detected in our analyses is CD206-positive macrophages, which are located at the base of crypts (Fig 6), express MafB (Fig 6) and IL10 (Supplementary Fig S5). These macrophages are likely to represent fully differentiated tolerogenic macrophages involved in sensing luminal antigen via sampling between intestinal epithelial cells, and contributing to epithelial renewal via the regulation of Lgr5 + stem cells 13,61 . The Cd206 macrophages appeared largely unaffected by IRF5 deficiency (Fig 7) and unlikely to be major contributors to the Hh-induced pathology 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Resident macrophages intimately associate with crypts, and when mice are treated with blocking antibodies against CSF1 (colony stimulating factor 1)-receptor, which in the intestinal crypt, are expressed by macrophages, stem cell survival is diminished and ISC lineage choice is skewed (Sehgal et al, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…Using CSF1R blockade to deplete macrophages that localize to the intestinal crypt epithelium, a recent study found that absence of macrophages results in reduced Lgr5 + intestinal stem cells, lysozyme-expressing Paneth cells and Peyer's patch M cells, and increased goblet cell density. 111 Macrophages have also been shown to be the likely source of IL-10 in a colon biopsy-induced injury model, and in this model, macrophage IL-10 induced epithelial synthesis of the pro-repair WNT1-inducible signalling protein 1 to mediate IEC proliferation and mucosal wound healing. 112 In DCs, transforming growth factor-b signalling has been suggested to control goblet cell numbers, mucus production and disease severity in dextran sulphate sodium colitis via Notch signalling, although the effects of DC dysfunction and involvement of other immune cell types were not fully investigated in this study.…”
Section: Immune Cell Contributions To Iec Differentiation and Functionmentioning
confidence: 93%
“…For instance, perturbations to macrophage–IEC interactions lead to aberrant differentiation of IEC subtypes. Using CSF1R blockade to deplete macrophages that localize to the intestinal crypt epithelium, a recent study found that absence of macrophages results in reduced Lgr5 + intestinal stem cells, lysozyme‐expressing Paneth cells and Peyer's patch M cells, and increased goblet cell density . Macrophages have also been shown to be the likely source of IL‐10 in a colon biopsy‐induced injury model, and in this model, macrophage IL‐10 induced epithelial synthesis of the pro‐repair WNT1‐inducible signalling protein 1 to mediate IEC proliferation and mucosal wound healing .…”
Section: Iec–immune Cell Crosstalkmentioning
confidence: 99%